Reading Materials in Hiligaynon and the Competency Level in Reading Comprehension of Grade 7 Students - MARCELINO, DURBIN (International Journal of Arts, Sciences and Education, 2025)
This study aims to examine the effect of using translated material in Hiligaynon in measuring the level of reading comprehension skills of Grade 7 students at Koronadal National Comprehensive High School for the school year 2023-2024. Participants in the research consisted of two sections of students, with 15 students in the experimental group and another 15 in the control group. The researcher employed the True Experimental Pre-test Post-test Group Design, wherein the experimental group used the translated material in Hiligaynon for reading, while the control group used the original Filipino text from Phil.IRI. To assess the impact of the Hiligaynon translated material on students’ comprehension levels, pre-tests and post-tests were administered. Based on the results, students’ reading comprehension levels were found to be disappointing.It was also proven that there was no significant difference in the comprehension levels of students before and after the instruction in both the experimental and control groups; no significant difference in the comprehension levels of students in the pre-test and post-test between the experimental and control groups; and no significant difference in the mean gain scores of the experimental and control groups. Overall, although students showed high acceptance of the translated material in Hiligaynon, it was still not enough to improve the reading comprehension of struggling readers. The researcher recommends modifying complex words in the Hiligaynon-translated material to enhance students’ understanding. It is also suggested to allocate sufficient time and an extended period for reading activities to help students develop their comprehension skills in terms of literal, interpretative, inferential, and evaluative understanding. Further studies may be conducted on other aspects beyond material acceptance to determine factors that can effectively improve reading comprehension.